Achievement and Aspiration of Local Colleges and Universities on the Research Agenda of Funding Institutions: Basis for Research Capability Building (American Journal of Interdisciplinary Research and Innovation, 2023)
This study was conducted for a specific purpose: to assess the research culture in the local colleges and universities and to propose an enhanced research capacity-building program. There were sixteen informants of this study; four administrators and twelve faculty members in the local colleges and universities in the CAMANAVA area namely: The University of Caloocan City, City of Malabon University, Navotas Polytechnic College and Valenzuela City Polytechnic College. A Purposive sampling technique was used to identify the informants. The study made use of a qualitative research approach. The data were collected from individual interviews with the administrators and faculty members. Using open coding, six (6) themes were emerged from the interviews and analysis of the document: philosophical research perspective, impact on institution’s growth and development, motivational components in research engagement, promoting the research culture, managing challenges and impediments and enhancing research capability. The informants identified the challenges in the development of the intensified research culture in the local colleges and universities which includes the scarcity of funds, research skills and expertise, network resources, and time constraint. These can be resolved through the enhancement of research capabalities and development programs. Generally, the study concluded that the research is indeed a powerful tool in addressing institutional problems and the utmost contribution of faculty members of the local colleges and universities in the academic and curricular programs and institutional growth and development. The institutional support will address the compelling need of the local colleges and universities to improve their research capability and research output.